"I Never Truly Thought About Them Having Friends": Equipping Schools to Foster Peer Relationships. (June 2017) - Leigers, Kelly; Kleinert, Harold L.; Carter, Erik W.
Students with severe disabilities often experience limited social participation and few friendships at school. We describe a project to equip school teams to implement peer support arrangements and peer networks focused on friendships, inclusion, and learning. We adopted a phenomenological qualitative approach to learn how participants viewed these interventions within their schools, issues emerging during implementation, and the impact of these interventions. We discuss themes surrounding (a) the impact of the context and structure of the school on implementation, (b) participants' views on professional development related to these interventions, and (c) impact on students, peers, and the broader school community.